High School Students’ Creative Writing Texts: Culture, Travel, Relationships, Life Incidents, and Asian Indian Epistemology - Iyengar, Dr. Kalpana Mukunda; Henkin, Dr. Roxanne.; Singh, Ms. Manaswita (IJRDO- Journal of Educational Research, 2016)
Gayathri Vidapeeth, Haridwar, India is an educational institution affiliated with Dev Sanskrithi Vishwavidyalaya (DSVV), Haridwar. In the summer of 2015, a delegation from the University of Texas at San Antonio (department of Interdisciplinary Learning and Teaching) offered professional development to instructors and students at DSVV through an invitational summer institute. The institute was modeled after the San Antonio Writing Project, a site network of the National Writing Project. One of the co-directors of the Haridwar Writing Project collected narratives from high school students at Gayathri Vidyapeeth after teaching classes using the writing workshop model for a week. In this study, the director, co-director, and a Haridwar Writing Project teacher consultant collaborated to analyze the data collected at the school. Data was analyzed utilizing four different approaches to narrative writing – Bruner’s ten features of narrative, Riessman’s thematic, and Frawley’s therapeutic and semantic scales analysis.